The Problem of the Legitimacy of War in the Context of Ethical Concepts: The Example of the 44-day War - Sargsyan, Armen (Conatus - Journal of Philosophy, 2023)
The article analyzes the issues of the legitimacy of war, the relationship between war and morality in the context of different ethical concepts. It is shown that the somewhat ‘fashionable’ notion of the ethics of war is actually problematic and does not clearly express the peculiarities of the relationship between war and morality. Analyzing the main conceptual discourses about war, it is argued that in some of them the acceptance of the legitimacy of war does not make sense with the logic of the watershed between war and morality. Analyzing the 44-day War separately for the first time in the context of the principles of the conception of just wars, it is argued that Azerbaijan’s military aggression against Artsakh was actually accompanied by a gross violation of many of these principles, despite the propaganda efforts of the Azerbaijani side to claim the opposite.